Integrating Emotions and Cognition Throughout the Lifespan - Labouvie-Vief, Gisela (Springer, 2016)
This book synthesizes the literature on emotional development and cognition across the lifespan. The book proposes a core language by which to describe positive and problematic developmental changes by recourse to a parsimonious set of core principles, such as elevations or declines in tension thresholds and their relation to the waxing and waning of the cognitive system over the life course. It integrates, similarly, the lifelong consequences of the positive or damaging aspects of the social milieu in fostering increases in tension thresholds with their advanced capacity for maintaining equilibrium and warding off stress versus a lowering of tension thresholds with disturbances of equilibrium maintenance and heightened susceptibility to stress and deregulation.